Effects of Parent-Children Communication on Academic Performance of the Children: A Study of Southern Punjab, Pakistan - Muhammad Bilal Bhatti, Noshina Saleem, Hanan Ahmed Mian, (JECCE, 2023)
This research was carried out to find the effects of parents-children communication on the academic performance of the children across Southern Punjab. This research investigated the relationship between parental-children communication, gender, and educational performance of the children. The researcher applied Social Learning Theory (SLT) by Albert Bandura (1977) and Emotional Security Theory (EST) by Cummings and Davies (1995). The researcher adopted quantitative research based on self-reported survey questionnaire from the school going students of 6th grade. The researcher used multistage sampling. Finally, the study was carried out on the sample of 1000 school children with a balanced sample of both male and female students. It was found that the unfriendly parent children communication effected the academic performance negatively and more than friendly parent children communication furthermore the male children were more affected by unfriendly parent-children communication than female children in context of their academic performance. The study concluded that academic performance of Southern Punjab children could be improved by increasing friendly parent-children communication and discouraging the unfriendly parent-children communication through awareness to the parents, however the socioeconomic status and low literacy levels of the parents remained one of the major factors which should be controlled.